TLR4-mediated chronic neuroinflammation has no effect on tangle pathology in a tauopathy mouse model - Basheer, Neha; Muhammadi, Muhammad Khalid; Freites, Carlos Leandro; Avila, Martin; Momand, Miraj Ud Din; Hryntsova, Natalia; Smolek, Tomas; Katina, Stanislav; Zilka, Norbert (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is characterized by a stereotypical accumulation of fibrillary aggregates composed of pathological tau proteins. Although neuroinflammation is commonly associated with tau pathology, the current preclinical evidence is insufficient to establish its direct causal role in tau tangle formation. This study aimed to determine whether chronic stimulation of Toll-like receptor 4 (TLR4), induced by a high dose of lipopolysaccharide (LPS, 5mg/kg), could exacerbate neurofibrillary tangle (NFT) pathology in a transgenic mouse model of sporadic AD expressing human truncated 151-391/3R tau. As expected, we observed a sustained elevation in the number of Iba-1 + -microglia in the LPS-treated group, compared with the sham group (p < 0.0001). Notably, there was a 1.5-1.7-fold increase in microglia per tangle-bearing neuron in the LPS-treated group. These microglia displayed a reactive yet exhaustive phenotype, evidenced by a significant decrease in cell area (p < 0.0001), without discernible changes in other morphometric parameters (perimeter, circumference, circularity, solidity, aspect ratio, or arborization degree). Despite the significant increase in reactive microglia, their phagocytic and clearance potential proved inefficient in reducing the tau hyperphosphorylation or tangle formation in the brainstem. Taken together, these findings suggest that chronic TLR4 stimulation in tau-transgenic mice does not affect the formation of tau tangles, despite extensive microglial activation.